Tingkat Responsivitas Aparatur Desa dalam Pelayanan Publik: Studi Kuantitatif di Desa Gerung Selatan, Kabupaten Lombok Barat - Fathurrahman, Ahmad; Zainul Hakim, Ahmad (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Public service delivery at the village level requires responsive officials who are able to address community needs effectively. Responsiveness is a key indicator of service quality, as it reflects the speed, accuracy, and attentiveness of public service providers. This study aims to examine the level of responsiveness of village officials in public service delivery in Gerung Selatan Village, West Lombok Regency. The research employs a quantitative approach using a survey design. Data were collected through structured questionnaires distributed to 150 community members who had accessed village public services. Responsiveness was measured using five indicators: service speed, timeliness, staff attentiveness, clarity of information, and responsiveness to public complaints. Data were analyzed using descriptive statistical techniques. The results indicate that the overall level of responsiveness of village officials is categorized as good, with an average score of 3.82. Staff attentiveness and clarity of information received the highest scores, while service timeliness showed the lowest score. These findings suggest that village officials demonstrate adequate responsiveness in service delivery, although improvements are still needed in service time consistency and complaint follow-up mechanisms. The study concludes that enhancing village public service responsiveness requires capacity building for village officials, standardized service procedures, and the development of a structured complaint management system.